2019
DOI: 10.4022/jafib.2208
|View full text |Cite
|
Sign up to set email alerts
|

Acute Procedural Complications of Cryoballoon Ablation: A Comprehensive Review

Abstract: Catheter ablation is increasingly performed for treatment of atrial fibrillation (AF). Balloon based procedures have been developed aiming at safer, easier and more effective treatment as compared to point to point ablation. In the present review article, we aimed to discuss acute procedural complications of cryoballoon ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 120 publications
0
5
0
2
Order By: Relevance
“… 1–3 The most common complication of this procedure is right PNI during ablation of the septal PVs. 9 , 11 , 12 In this case, the freezing cycle needs to be immediately interrupted to avoid further damage of the PN. 10 , 13 Moreover, many protocols aim for no additional cryoablation attempt at the level of the right PVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1–3 The most common complication of this procedure is right PNI during ablation of the septal PVs. 9 , 11 , 12 In this case, the freezing cycle needs to be immediately interrupted to avoid further damage of the PN. 10 , 13 Moreover, many protocols aim for no additional cryoablation attempt at the level of the right PVs.…”
Section: Discussionmentioning
confidence: 99%
“…Phrenic nerve injury (PNI) is the most frequent procedural complication in CB-based PVI, with an incidence ranging from 1.1 to 6.2% of patients, and it is more common during isolation of the septal PVs. 2 , 3 , 9–12 Considering that most ablation protocols aims for an immediate stop of energy delivery, as well as no further ablation attempt for the right PVs, PNI occurrence might increase the risk of PV electrical reconnection and consequently the arrhythmia recurrence. 4 , 13 The data are sparse regarding the reconnection in patients who suffer PNI during CB-based PVI.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta‐analysis of 14 randomized controlled studies and 34 observational studies comparing the safety of cryoballoon versus radiofrequency ablation procedure, the cryoballoon ablation group had a lower incidence of pericardial effusion and cardiac tamponade (relative risk, 0.58) compared with radiofrequency ablation group. 28 It was postulated that the extreme manipulation of catheter or probe devices within the cardiac chambers 13 and poor trans‐septal puncture technique 13 , 29 , 30 , 31 , 32 are the major contributing factors to cardiac perforation. While most cases are mild and asymptomatic, 33 the development of hemodynamic instability should warrant a strong suspicion of a possible cardiac tamponade.…”
Section: Discussionmentioning
confidence: 99%
“…The Japanese Heart Rhythm Society emphasized the risk of air embolism during cryoballoon ablation in 2018. In addition, a comprehensive review suggested the importance of detecting and managing air embolism [ 12 ]. An ex vivo study revealed that air intrusion, the cause of air embolism, is associated with the following two factors: the catheter system (comprising catheters of different vascular diameters) and the negative pressure in the sheath [ 13 ].…”
Section: Discussionmentioning
confidence: 99%